Factors Associated with Frailty Syndrome in the Elderly: A Systematic Review - Jamilatur Rasyidah Efendi; Etty Rekawati; Henny permatasari; Utami Rachmawati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Frailty syndrome is a common condition among the elderly. Frailty has become a major health issue in the 21st century, affecting older adults and being associated with various negative outcomes such as decreased quality of life, increased mortality, hospital admissions, risk of falls, depression, and dementia. Objective: This study aims to identify and summarize the factors associated with frailty syndrome in the elderly through a systematic literature review. The findings are expected to serve as a basis for early prevention and management efforts of frailty in older adults. This study employs a systematic literature review method by analyzing 7 relevant journal articles published between 2020 and 2025. Articles were sourced from databases such as ProQuest, SpringerLink, and ClinicalKey for Nursing, selected based on topic relevance and publication quality to provide a comprehensive overview of the factors influencing frailty syndrome in the elderly. Based on the review of 7 journal articles, several factors influencing frailty syndrome were identified, including: age over 80 years, polypharmacy (use of multiple medications), gender, low body mass index (BMI), history of hospitalization, previous alcohol use, history of falls, living alone, presence of comorbidities, and impaired cognitive function. Frailty syndrome in the elderly is influenced by various risk factors spanning physical, psychological, and social aspects. Identifying these factors is crucial to support early interventions and preventive efforts, thereby improving the quality of life of older adults and reducing the risk of further complications. This systematic review can serve as a reference in developing strategies for the prevention and management of frailty among the elderly population.